Energetic potential of piggery effluent by anaerobic digestion [Resumo] - Eusebio, Ana (2019)
ABSTRACT: The sector of pig farming in Portugal is looking for sustainable and practical solutions to overcome existing environmental problems caused by very polluting discharges of effluents in rivers and wastewater treatment plants. The anaerobic digestion (AD) is a suitable process used to treat an organic effluent and, simultaneously, provide the agricultural and energetic valorisation of the substrate. The main objective of this work was to evaluate the energetic potential of a piggery effluent, collected in a pig farm with 9,000 animals, estimated in a volume of 900-1,170 m3 d-1. Anaerobic digestion assays were carried out in batch mode, under anaerobic and mesophilic conditions.